2004
DOI: 10.1007/s11661-004-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Temperature evolution and life prediction in fatigue of superalloys

Abstract: Low-cycle fatigue behavior of two superalloys, ULTIMET ® alloy, Co-26 pct Cr-9 pct Ni (wt pct), and HAYNES ® HR-120 ® alloy, Ni-33 pct Fe-25 pct Cr, was studied at room temperature. An infrared thermography system was employed to monitor the temperature evolution of fatigue processes for both superalloys. Temperature changes during fatigue were related to the hysteresis effect, and were successfully predicted, based on the consideration of the hysteresis effect and heat conduction. The temperature increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 17 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…The shorter fatigue lives in mercury at 10 than at 0.2 Hz were only found at the higher stress levels (Ն230 MPa) induced by the temperature effect (130 °C at 10 Hz vs 20°C at 0.2 Hz) ( Figure 7). However, at lower stress levels (Ͻ230 MPa), the temperature increase is generally lower, [47][48][49][50][51][52] and, thus, there were comparable temperatures at 10 and at 0.2 Hz, which resulted in similar fatigue lives at lower stresses (Figure 7).…”
Section: Discussionmentioning
confidence: 96%
“…The shorter fatigue lives in mercury at 10 than at 0.2 Hz were only found at the higher stress levels (Ն230 MPa) induced by the temperature effect (130 °C at 10 Hz vs 20°C at 0.2 Hz) ( Figure 7). However, at lower stress levels (Ͻ230 MPa), the temperature increase is generally lower, [47][48][49][50][51][52] and, thus, there were comparable temperatures at 10 and at 0.2 Hz, which resulted in similar fatigue lives at lower stresses (Figure 7).…”
Section: Discussionmentioning
confidence: 96%
“…The temperature sensitivity is 0.015 at 23 8C, while the spatial resolution can be as small as 5.4 mm [19][20][21][22][23][24][25]. The system has a maximum dataacquisition speed of 120 Hz at a full frame of 320!256 pixels and 38,400 Hz at 16!16 pixels.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Guo et al showed a decrease of temperature present in phase II for AZ31B magnesium alloy. Jiang et al obtained a steady‐state phase II for lower loading levels and a linear increase for higher levels, for ULTIMET alloy and HAYNES HR‐120 alloy. The absence of stabilisation in phase II was taken into account in the accelerated method of fatigue life curve determination for different materials for rotary bending and uniaxial tension‐compression …”
Section: Plastic Strain Energy Determination Using Thermographic Analmentioning
confidence: 99%